Quality indicators of college faculty members in three institutions of higher learning in the city of Dagupan - Baun, Alice Ilalo S. 1947-; Luzon Colleges, Dagupan City; Northwestern Educational Institution, Dagupan City; University of Pangasinan, Dagupan City (1973)
Data for this study were gathered by means of questionnaire issued to 286 faculty-respondents and checklist answered by three administrative-respondents in the three institutions. About 89 of the faculty members are bachelor's degree holders, while 10 are holders of master's degrees and two have doctoral degrees; about 261 have government eligibilities. The average subject load was four. Aside from teaching responsibilities, they handled non-academic jobs.
Thesis (M. Ed.)--University of the Philippines.
Keywords: College teachers -- Dagupan City